2015
DOI: 10.1021/acs.energyfuels.5b02246
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effect of Asphaltene Types on the Interfacial Tension of CO2–Hydrocarbon Systems

Abstract: Interfacial tension (IFT) is known as the critical parameter affecting the efficiency of CO 2 flooding during the enhanced oil recovery (EOR) process. Besides, the asphaltene precipitation phenomenon is reported as the most significant problem during CO 2 injection into asphaltenic oil reservoirs. Accordingly, it is important to examine the effect of asphaltene precipitation on the IFT behavior of the oil−CO 2 system at reservoir conditions. The main objective of this research work is to study of the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…Another possible reason for the abovementioned observation could be the precipitation and deposition of asphaltene of the oil which have been reported in various CO 2 EOR studies. 18,29,30 However, several results presented in previous investigations using the same crude oil used in this study and under conditions similar to those of the experiments reported here have shown that the contact of CO 2 and the oil did not result in the precipation or deposition of the asphaltene fraction of the oil in porous media. 26 Therefore, it appears that the precipitation or deposition of asphaltene would have not been the case in our experiments.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…Another possible reason for the abovementioned observation could be the precipitation and deposition of asphaltene of the oil which have been reported in various CO 2 EOR studies. 18,29,30 However, several results presented in previous investigations using the same crude oil used in this study and under conditions similar to those of the experiments reported here have shown that the contact of CO 2 and the oil did not result in the precipation or deposition of the asphaltene fraction of the oil in porous media. 26 Therefore, it appears that the precipitation or deposition of asphaltene would have not been the case in our experiments.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…The particles tend to accumulate at the interfaces, which can increase the interfacial activity of colloidal solutions. This particles accumulation can occur at the oil–CO 2 interface, which leads to IFT alteration. , Therefore, it is concluded that large molecules of asphaltenes begin to aggregate at the CO 2 –oil interface, which causes the IFT to slightly increase in the high pressure range. Because of the asphaltene agglomeration, the asphaltene film is formed at the oil–CO 2 interface and modifies the IFT–pressure trend by compensation of the effect of CO 2 solubility, as shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…There is a lack of a systematic quantitative characterization method of gel CO 2 responsiveness in order to screen out the ideal CO 2 responsive gel. Moreover, CO 2 -responsive groups can be used not only in the preparation of CO 2 -responsive gels, but also in the preparation of CO 2 -responsive ionic solutions, which have broad application prospects in the field of CO 2 capture [128,129]. (3) The current CO 2 -responsive gels are based on the mechanism of protonation of the CO 2 responsive groups, which causes the volume expansion of the gels, and thus seal the CO 2 migration channel of the formation.…”
Section: Further Development Of Co 2 Responsive Gels and Concluding R...mentioning
confidence: 99%